Reading habits, interests and information needs of users of the Palayan City Public Library and Information Center with implications for strengthening its information services - Estigoy, Consuelo J.; Sison, Josephine C.; Yang, Jackson V. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1999)
This study focused on determining the reading habits, interests and information needs of the residents in Palayan City, Nueva Ecija to strengthen its information services. Specifically, the study aimed to determine the following: the socio-demographic profile of Palayan City according to age, sex, civil status, population, literacy level, educational status and occupational patterns; the reading habits, interests and information needs of the community; sources of their reading materials; awareness of the existence of the public library and information center and identifying the persons responsible for maintaining and financing the public library. The following fifteen barangays of the city were covered in the survey: Atate, Aulo, Caballero, Caimito, Ganaderia, Imelda Valley, Malate, Maligaya, Manacnac, Mapaet, Marcos Village, Militar, Santolan, Sapang Buho and Singalat. The respondents were those ages 18-60 years old, male or female, who may or may not be employed. The descriptive statistics using statistical inference was used in this study. A very high turn-out of the questionnaires (92) were retrieved an indication that the respondents were cooperative.
The findings show that the population are literate . Majority speak Tagalog. Most of the population indicated that books are found in their households as reading materials. The three top favorite hobbies were watching television, listening to the radio and reading. Since the group is literate, the degree of interest in reading is high. The books including the Bible and Tagalog novelas are the reading materials of the population. The news section of the newspapers are mostly read, manifesting that they are also curious about current events. The population buy their reading materials. Many of them go to school libraries. The three main sources of information are radio, newspapers and books, The population want to have books, newspapers and magazines in the public library. However, they also wish that religious materials be found in the public library. Majority of the population are not aware of the existence of the public library, showing a lack of information campaigns on its operations and services. The preferred information on livelihood are those on ricefield development, cultivation of land and cooking, a manifestation that the respondents are interested in upgrading their agricultural knowledge, since it is the main source of income in Nueva Ecija. The population are willing to support the development and maintenance of the library. Majority of the respondents indicated that the government should support the library with the help of individuals and Non-Government Organizations (NGO).
Among the recommendations of the study are: a final resolution should be filed by the City council to formally establish the existence of the public library and use to tie-up with the National Library for providing the initial book allocation. Information dissemination should also be done to inform the community about the services available from the Palayan City Public Library. The local government should allocate regular funding for the collection development of the library. The out-of-school youth should be involved with its activities. An additional expansion of the library should also be considered, that are in consonance with the standards of a public library. A Children's Section should also be provided. a professional librarian should also be hired to manage the library. The librarian-in-charge should coordinate with the Department of Education, Culture and Sports (DECS) to supplement the reading materials of school libraries. Tapping other organizations like government organizations, universities, wealthy individuals and NGOs should be undertaken to develop the library's collections. And finally, the implementation of the proposed five-year development plan to meet the minimum standards for public libraries by the year 2005.
Thesis (M.L.S.)--University of the Philippines, Diliman
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Library use studies--Philippines--Palayan City (Nueva Ecija).; Palayan City (Nueva Ecija). Library--Information services; Reading interests--Philippines--Palayan City (Nueva Ecija).